Analisis Dampak Kemasan, Promosi, Citra Merek terhadap Minat Beli Air Minum dalam Kemasan di Kota Surabaya - Franz Jingga Theng; Sri Nathasya Br Sitepu; Irantha Hendrika Kenang (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
Bottled water is one of the beverage variants sought by consumers. Bottled water comes in several brands and sizes on the market. This study analyzes one relatively new bottled water (Aquaviva) that has been circulating on the market since 2022. New products require a marketing strategy to dominate the market competition. Analysis of the impact of packaging, promotion, and brand image are important variables on the purchasing interest of bottled water (Aquaviva) among potential consumers in Surabaya. This study uses a quantitative method to collect primary data for analysis. The population of Surabaya is the study population, but the data is not known for certain. This led to sample selection based on certain criteria. The study sample consisted of 150 people who completed a questionnaire on Google Form offline. The analysis used multiple linear regression with the help of SPSS software. The analysis found that the independent variables of brand image, packaging, and promotion influence the dependent variable (purchase interest of bottled water (Aquaviva) in Surabaya.